Error concealment Pada Transmisi Video H.264/AVC dengan Frequency Selective Extrapolation - Ananda, Fitri Elvira (Jurnal Fokus Elektroda : Energi Listrik, Telekomunikasi, Komputer, Elektronika dan Kendali), 2021)
Video transmission is encoded by block-based techniques such as MPEG in sensitive environment. It’s very susceptible to noise which can cause block losses and even missing frames during transmission. A technique to overcome this problem is applied Error concealment (EC) on the decoder. There are two approaches used in this EC, spacial EC which utilizes information around the image and temporal EC by utilizing motion information. The method of EC that used in this research is Frequency Selective Extrapolation (FSE). The video is encoded by the H.264 / AVC standard (MPEG-Part10). The isolated block losses was added to the video as an error simulation, then applied the EC-FSE method on the decoder. There are two method of EC-FSE used, FSE-2D (two dimensions) and FSE-3D (three dimensions). The measurement results were observed by the PSNR and MOS values. The simulation results show that H.264 / AVC video concealed with FSE-3D has a better performance than FSE-2D.